BIM-based architectural analysis and optimization for construction 4.0 concept (a comparison) - Jie Zhang; Xuping Zhu; Abdul Mateen Khan; Moustafa Houda; Sardar Kashif Ur Rehman; Mohammed Jameel; Muhammad Faisal Javed; Raid Alrowais (Ain Shams Engineering Journal, 2023)
The growing need for electricity has put Pakistan's burgeoning economy in peril. The notion of “Construction 4.0″ is considered in this study since it enables the greatest utilization of energy and architectural analysis. A case study and a method for building information modelling are used to analyze the concepts of green building. The case study building is represented as a parametric model using the Autodesk Revit platform with the original blueprints and data. Using Autodesk Insight 360, an energy analysis and comparison of optimization case study of the A-Block and Z-Block COMSATS Abbottabad, Pakistan is chosen. This study analyses an academic building's energy performance as a case study to reduce energy usage. By turning the building 360 degrees at 45-degree intervals and utilizing BIM to install energy-efficient construction materials, this study analyses the energy efficiency of an academic building. The average annual energy cost for blocks A and Z is decreased from 228 kWh/m2 to 160 kWh/m2 and 192 kWh/m2, respectively.